A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia - Kimura, Seishi; Johnson, G. David; Peristiwady, Teguh; Matsuura, Keiichi (Zootaxa, 2017)
A new genus and species of the percoid family Symphysanodontidae, Cymatognathus aureolateralis are described based on three specimens collected from North Sulawesi, Indonesia. The new species shares with the confamilial genus Sym-physanodon the unique supraneural and spinous dorsal-fin pterygiophore insertion pattern usually of 0/0/0+2+1/1/, T-shaped first supraneural, foreshortened base of the penultimate ventral procurrent caudal-fin ray, well-developed outer tooth patches at anterior tips of both jaws as well as along the medial surface of most of the length of the coronoid process of the dentary. The new species, however, is distinguishable from members of Symphysanodon by the following diagnostic characters: posterior tip of coronoid process of dentary abruptly depressed, so that teeth on anterior portion appear as an elevated patch, anterior tip of upper jaw not notched, and posterior nostril horizontally slit-like. Although the new species superficially resembles the members of the genus Giganthias (Giganthiidae) and some members of the subfamily Anthiadinae (Serranidae) in the unique characters it shares with Symphysanodon, it differs from Giganthias in having the above-mentioned unique pterygiophore insertion pattern and tips of all dorsal- and pelvic-fin spines smooth (vs. pterygiophore insertion pattern 0/0/2/1+1/1/, and tips of second, third and/or fourth dorsal- and pelvic-fin spines serrated), and from the members of Anthiadinae in having two flat opercular spines (vs. three) and 10 + 15 = 25 vertebrae (vs. 10 + 16–18 = 26–28). A revised diagnosis of the Symphysanodontidae is presented.